Botswana's HIV response: Policies, context, and future directions. Issue 3 (17th January 2020) - Ramogola‐Masire, Doreen; Poku, Ohemaa; Mazhani, Loeto; Ndwapi, Ndwapi; Misra, Supriya; Arscott‐Mills, Tonya; Blank, Lilo; Ho‐Foster, Ari; Becker, Timothy D.; Yang, Lawrence
Abstract: This brief report describes key periods in the history of the national public health response to the human immunodeficiency virus (HIV) epidemic in Botswana. It reveals the context leading to the development of HIV policies presently in place and current challenges that remain. The report concludes with opportunities for future directions, initiatives, and policy changes to reduce the high rates of HIV.